PENDAMPINGAN PENGEMBANGAN DESA WISATA BERBASIS EKONOMI KREATIF DAN PARTISIPASI MASYARAKAT DI DESA PECATU - Putu Ratna Windusara Putri; I Made Wisnu Wardana; I Made Sujana; Fahmi Tanjung (Yayasan Nusantara Hasana Berdikari, 2024)
Tourism Village Development Has Become An Effective Strategy For Promoting Local Economic Growth And Improving Community Welfare. Pecatu Village, Located In Badung Regency, Bali, Possesses Significant Tourism Potential Supported By Natural Attractions, Cultural Heritage, And Community Creativity. However, The Optimization Of These Potentials Still Faces Several Challenges, Including Limited Tourism Management Capacity, Lack Of Creative Economic Product Diversification, And Insufficient Community Involvement In Tourism Village Development. This Community Service Program Aimed To Strengthen Community Capacity Through Assistance In Developing A Tourism Village Based On The Creative Economy And Community Participation. The Methods Employed Included Socialization, Training, Mentoring, Focus Group Discussions (Fgds), And Program Evaluation. Participants Consisted Of Local Msme Actors, Tourism Awareness Groups, Village Officials, And Community Members Totaling 35 Participants. The Results Indicated An Increase In Community Understanding Of Tourism Village Management, Creative Economy Development, Digital Marketing Strategies, And The Importance Of Community Participation In Sustainable Tourism Development. Furthermore, Participants Successfully Identified Tourism Potentials And Formulated A More Structured Tourism Village Development Plan. This Program Positively Contributed To Strengthening Community Capacity In Supporting The Sustainability Of Tourism Village Development In Pecatu Village.